Performance enhancement of Hitec molten salt through TiB2 and ZrB2 nanoadditives for High-Temperature TES and CSP applications - Gurgenc, Ezgi; Yamac, Halil ibrahim; Oztop, Mesut; Ozabaci, Murat; Canbay, Canan Aksu; Gurgenc, Turan; Öztop, Hakan Fehmi (Elsevier, 2026)
Hitec molten salt (7NaNO3-53KNO3-40NaNO2) is widely considered for high-temperature heat transfer and thermal energy storage, yet its relatively limited heat storage capacity and thermal transport performance constrain energy density and charging-discharging efficiency in CSP-TES systems. To address this limitation, Hitec was modified with TiB2 and ZrB2 nanoparticles at loadings of 0.5, 1, 1.5, and 2 wt% and investigated through a comprehensive experimental framework. Phase integrity and chemical stability were examined by Xray diffraction and Fourier transform infrared spectroscopy. Microstructural features, nanoparticle distribution, and elemental homogeneity were evaluated using FE-SEM/EDX. Thermophysical behavior was characterized by DSC to determine specific heat capacity and melting-solidification characteristics, while thermal stability was assessed by TGA. Thermal conductivity was measured using the transient plane source method. ZrB2 provided the strongest heat storage enhancement. Solid-phase Cp increased from 1.44 to 2.22 J g- 1 degrees C- 1 and liquid-phase Cp increased from 1.51 to 2.47 J g- 1 degrees C- 1 at 1 wt% ZrB2, corresponding to improvements of 54.68% and 63.30%. TiB2 delivered the largest heat-transfer improvement, increasing thermal conductivity from 0.951 to 1.664 W m- 1 K- 1 at 2 wt% (74.97%). Melting enthalpy increased by up to 16.93% for TiB2 and 21.13% for ZrB2. Thermal stability improved substantially, shifting the decomposition onset from 612 degrees C (Hitec) to 661 degrees C and 673 degrees C for 2 wt% TiB2 and ZrB2, respectively. Overall, TiB2 and ZrB2 exhibit complementary performance profiles, enabling tailored Hitec-based media for higher energy density, improved heat transfer, and extended high-temperature operation in CSP-TES and related thermal management applications.
Keywords: Hitec; Boride; Nanocomposite PCM; Thermal conductivity enhancement; Thermal energy storage; CSP